Pengaruh Kombinasi Keunggulan dan Keterbatasan Perusahaan terhadap Set Kesempatan Investasi (IOS) - GAGARING PAGALUNG (The Indonesian Journal of Accounting Research, 2013)
This paper examined the relationship between the model of growth opportunities rests on combining the firm advantages and limitations, and the investment opportunity set (IOS). In particularly, I extend and modify the work of AlNajjar and Belkaoui (2001) for Indonesian conditions. Four variables are used as firm advantages such as corporate reputation, multinationality, size and profitability, and two variables as firm limitations such as leverage and systematic risk. I find evidence that only one variable of firm advantages such as corporate reputation, and two variables of firm limitations are confirmed with the general model of growth opportunities. Nevertheless, the relationship between leverage and IOS are directly related, where this relation are not consist with the theory.